Peningkatan Pemasaran Objek Wisata Kalimosodo melalui Strategi Digital Marketing di Kecamatan Tulung, Klaten - Bimo, Djoko Sri; Paramitasari, Ratih; Budiwati, Yulia; Fadloli, Fadloli (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Kalimosodo tourist attraction, located in Tulung District, Klaten Regency, holds great potential as a natural and cultural tourist destination. Unfortunately, this attraction has not been matched by an adequate marketing strategy, especially in the digital context. This has led to low tourist visits and minimal exposure on online platforms. Based on the identification of partner problems, assistance is needed that focuses on strengthening digital marketing skills to improve the promotion of tourist destinations effectively and efficiently. This service activity uses the Asset-Based Community Development (ABCD) approach which is oriented towards developing local potential and assets. The implementation method is in the form of socialisation of the importance of digital marketing, as well as workshops on content creation, social media management, and promotion strategies based on local distinctiveness. This activity is carried out in a participatory manner so that partners can understand and practice the material provided directly. This process is also accompanied by evaluation and technical assistance in managing promotions on an ongoing basis. The results of the activity show that partners have increased understanding and skills in using social media as a marketing tool.Tourism promotion accounts were successfully created, and digital content began to be uploaded consistently. The conclusion of this activity is that the application of digital marketing in a structured and community-based manner can increase the existence of local tourism objects. The ABCD approach is a relevant strategy to empower communities to manage tourism promotion independently and sustainably.